Engineering geological investigation of trail bridges in western Nepal (Journal of Nepal Geological Society, 2002)
The study covers the engineering geological investigation of eight bridges: Kailashmandu (Bajura district), Khaniya Ghat (Baglung district), Listra Bagar (Bajhang district), Kunalo Gad (Bajura district), Samar (Mustang district), Lode Ghat (Achham district), Puima Gad (Humla district) and Ghatte Gad (Darchula district) of western Nepal. The study was carried out in conceal with the manual and checklist developed by HELVETAS as far as practicable. The present study intended to overwhelm the incompatibility, constraint and limitations of manuals and checklist of SBD by applying the suitable recent methods of engineering geology. During the field observation, the risk of possible bridge failure due to geological and geotechnical conditions was significantly reduced by using the actual rock and soil index parameters obtained from the laboratory test instead of the empirical range values given in the SBD MANUAL. Similarly, the bridge construction cost was also abridged in some extent.